Does 2‐phosphoglycolate serve as an internal signal molecule of inorganic carbon deprivation in the cyanobacterium Synechocystis sp. PCC 6803?. (7th January 2015) - Haimovich‐Dayan, Maya; Lieman‐Hurwitz, Judy; Orf, Isabel; Hagemann, Martin; Kaplan, Aaron
Summary: Cyanobacteria possess CO2 ‐concentrating mechanisms (CCM) that functionally compensate for the poor affinity of their ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco) to CO2 . It was proposed that 2‐phosphoglycolate (2PG), produced by the oxygenase activity of Rubisco and metabolized via photorespiratory routes, serves as a signal molecule for the induction of CCM‐related genes under limiting CO2 level (LC) conditions. However, in vivo evidence is still missing. Since 2PG does not permeate the cells, we manipulated its internal concentration. Four putative phosphoglycolate phosphatases (PGPases) encoding genes ( slr0458, sll1349, slr0586 and slr1762 ) were identified in the cyanobacterium S ynechocystis PCC 6803. Expression of slr0458 in E scherichia coli led to a significant rise in PGPase activity. A S ynechocystis mutant overexpressing (OE) slr0458 was constructed. Compared with the wild type (WT), the mutant grew slower under limiting CO2 concentration and the intracellular 2PG level was considerably smaller than in the wild type, the transcript abundance of LC‐induced genes including cmpA, sbtA and ndhF3 was reduced, and the OE cells acclimated slower to LC – indicated by the delayed rise in the apparent photosynthetic affinity to inorganic carbon. Data obtained here implicated 2PG in the acclimation of this cyanobacterium to LC but also indicated that other, yet to be identified components, are involved.